Anti-asthmatic activity of alkaloid compounds from Pericarpium Citri Reticulatae (Citrus reticulata 'Chachi'). Issue 2 (29th January 2019) - Fu, Manqin; Zou, Bo; An, Kejing; Yu, Yuanshan; Tang, Daobang; Wu, Jijun; Xu, Yujuan; Ti, Huihui
Abstract : Pericarpium Citri Reticulatae (PCR, Citrus reticulata 'Chachi', Guangchenpi in Chinese) is one of the most famous Chinese citrus herbal medicines. Abstract : Pericarpium Citri Reticulatae (PCR, Citrus reticulata 'Chachi', Guangchenpi in Chinese) is one of the most famous Chinese citrus herbal medicines. The in vivo anti-asthmatic activity of 'Chachi' PCR was investigated using a histamine-induced experimental asthma model in Guinea pigs. Two alkaloid-type compounds, synephrine and stachydrine, were analyzed and identified in the 'Chachi' PCR alkaloid fraction. The alkaloid fraction and synephrine protected Guinea pigs against histamine-induced experimental asthma in a dose-dependent manner. The respective application of high, middle, and low doses of the 'Chachi' PCR alkaloid fraction significantly increased specific airway resistance by 284%, 328%, and 355%, and decreased dynamic compliance by 57%, 67%, and 75%. A similar change was observed for synephrine. The expression of eosinophils in bronchoalveolar lavage fluid (BALF) and serum IgE, IL-4, and IL-5 levels in histamine-induced experimental asthmatic Guinea pigs were significantly downregulated by the 'Chachi' PCR alkaloid fraction and synephrine compared to the control group, whereas stachydrine did not impart a statistically significant effect on the expression of tested inflammatory cells (leucocytes, eosinophils, neutrophils, and lymphocytes), immunoglobulin (IgE), or cytokines (IL-4 and IL-5). Pathological changes in lung tissues in each treatment group included the infiltration of inflammatory cells around the bronchia.